INTERMITTENT FASTING EFFECT IN OBESITY : HEALTH MANAGEMENT IN OBESITY - Mardhotillah, Hanifah (Politeknik Kesehatan Kuningan Medical Center, 2025)
Urbanization period is one of the main factor causing obesity problems in society. Obesity is a global health problem that is identical to the accumaltion of excess fat in the body. The application of calori restriction through the intermittent fasting approach is a widely discussed issue because people tend to help people with obesity lose weight. This literature study aims to determine the extent of the positive benefits of intermittent fasting on obesity conditions. This study was conducted using a literatur reviewe method using the Pubmed and Google Scholar database with the keywords Intermittent Fasting and Obesity using the boolean search technique. The inclusion criteria for this literature are articles published in the last 10 years namely 2014 – 2024, randomized controlled trial (RCT) method, in English, subject aged >18 years with obesity nutritional status, providing interventions in the form of intermittent fasting with a minimun intervention of one month with a minimun sample size of 20 people. Articles are selected individually through a double process that refers to three main criteria for research quality. The results of the literature show that the application of intermittent fasting provides positive benefits through wegith loss, decreased blood pressure, lipid profiles, reduced inflammation and improved gastrointestinal microbiota. Implementation of intermittent fasting can be a strategy in obesity health management.